2021
DOI: 10.1111/jcpt.13524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different remifentanil target concentrations on MAC BAR of sevoflurane in patients with liver dysfunction under carbon dioxide pneumoperitoneum stimulus: A randomized controlled trial

Abstract: What is known and objective Remifentanil can effectively decrease the sevoflurane concentration to block sympathetic adrenergic response to CO2 pneumoperitoneum stimulus,and liver dysfunction will significantly reduce the MACBAR (minimum alveolar concentration for blocking adrenergic response) of sevoflurane. However, the effects of different remifentanil concentrations on the MACBAR of sevoflurane in patients with liver dysfunction are unclear. The aim of this study was to observe the effects of different rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is often used to evaluate the potency of inhalational anesthetics. Pre-pilot studies by our research team have demonstrated that opioids signi cantly reduce the MACBAR of inhalation anesthetics (2)(3)(4)(5). Other sedatives and analgesics also reduce the MACBAR of inhalation anesthetics to varying degrees (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is often used to evaluate the potency of inhalational anesthetics. Pre-pilot studies by our research team have demonstrated that opioids signi cantly reduce the MACBAR of inhalation anesthetics (2)(3)(4)(5). Other sedatives and analgesics also reduce the MACBAR of inhalation anesthetics to varying degrees (6).…”
Section: Introductionmentioning
confidence: 99%